2016
DOI: 10.1007/s40292-016-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lifestyle and Systemic Arterial Hypertension in Young Adults: A National, Survey-Based, Cross-Sectional Study

Abstract: High BP values were found in 11 % young adults. Male sex, adiposity and alimentary habits were the main determinants of high BP values, indicating that young men are a suitable target for healthy lifestyle interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 45 publications
4
15
0
5
Order By: Relevance
“…24 A study conducted by Papathanasiou et al found that body mass index and male gender had higher odds of being hypertensive in this age group. 23 Similar findings were postulated by study conducted by Bruno et al 25 In our study, we found a higher prevalence of hypertension in males when compared to females, but it did not attain the level of significance. Similar results were reported by a study conducted by Reddy et al 27 But, a study conducted by Papathanasiou et al found higher prevalence of hypertension in males when compared to females.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…24 A study conducted by Papathanasiou et al found that body mass index and male gender had higher odds of being hypertensive in this age group. 23 Similar findings were postulated by study conducted by Bruno et al 25 In our study, we found a higher prevalence of hypertension in males when compared to females, but it did not attain the level of significance. Similar results were reported by a study conducted by Reddy et al 27 But, a study conducted by Papathanasiou et al found higher prevalence of hypertension in males when compared to females.…”
Section: Discussionsupporting
confidence: 89%
“…29,[31][32][33][34] After logistic analysis, age and overweight category were found to be independent risk factors associated with hypertension. Similar inferences were found by Papathanasiou et al and Bruno et al 23,25 Some studies conducted on pre hypertension as the outcome variable also found similar results. In our study, physical activity was found not associated with hypertension, but study conducted by Papathanasiou et al found physical activity to be protective for hypertension.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…During these periods, we observed that hypertension [4]. At the same time, another analysis was aimed at evaluating hypertension prevalence and control in a large cohort of young individuals screened during the 2014 edition of the WHD, and assessing the potential correlations with lifestyle attitudes [5]. Data were collected in 13 excellence centers distributed across the whole national territory and referred to about 500 young individuals aged less than 18 years, among whom hypertension prevalence was 11 % [5].…”
mentioning
confidence: 99%
“…At the same time, another analysis was aimed at evaluating hypertension prevalence and control in a large cohort of young individuals screened during the 2014 edition of the WHD, and assessing the potential correlations with lifestyle attitudes [5]. Data were collected in 13 excellence centers distributed across the whole national territory and referred to about 500 young individuals aged less than 18 years, among whom hypertension prevalence was 11 % [5]. These relevant and updated findings have been obtained with the support of the Italian Society of Hypertension (SIIA), which was very active and deeply involved in the annual organization of the WHD.…”
mentioning
confidence: 99%